2017
DOI: 10.3389/fnhum.2017.00401
|View full text |Cite
|
Sign up to set email alerts
|

Neural Signatures of Rational and Heuristic Choice Strategies: A Single Trial ERP Analysis

Abstract: In multi-attribute choice, people use heuristics to simplify decision problems. We studied the use of heuristic and rational strategies and their electrophysiological correlates. Since previous work linked the P3 ERP component to attention and decision making, we were interested whether the amplitude of this component is associated with decision strategy use. To this end, we recorded EEG when participants performed a two-alternative choice task, where they could acquire decision cues in a sequential manner and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Considerable research indicated that human brain was especially sensitive to negative information since the salient of valence, and that the negative information is preferentially processed relative to neutral and positive events ( Huang and Luo, 2006 ; Yuan et al, 2007 ; Gui et al, 2016 ). The higher N1 amplitude suggests that individuals pay more attention on this choice item at the early stage during the decision process ( Wichary et al, 2017 ). Thus, the enhance N1 reflected that the negative information attracted people much attention early during the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research indicated that human brain was especially sensitive to negative information since the salient of valence, and that the negative information is preferentially processed relative to neutral and positive events ( Huang and Luo, 2006 ; Yuan et al, 2007 ; Gui et al, 2016 ). The higher N1 amplitude suggests that individuals pay more attention on this choice item at the early stage during the decision process ( Wichary et al, 2017 ). Thus, the enhance N1 reflected that the negative information attracted people much attention early during the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed that brain regions such as the central and parietal region was recruited during the early stages of valence-related information processing ( Gui et al, 2016 ). The higher N1 amplitude suggests that individuals pay more attention on the valence of choice item very early during the decision process ( Wichary et al, 2017 ). Crucially, the amplitude variation of P300, which is a positive wave peaking roughly 300–500 ms at central and parietal electrodes ( Gu et al, 2011 ; Wang et al, 2017b ), is a typical ERP component in social decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…LMMs allow the inclusion of single trials in one group analysis, thus it is an ideal choice for combining EEG and fMRI measures. This analysis is less prone to Type I and II errors than traditional methods (Aarts, Verhage, Veenvliet, Dolan, & van der Sluis, 2014;Wichary, Magnuski, Oleksy, & Brzezicka, 2017). In this model, the individually normalized (z-scored) gamma value was treated as a predictor, whereas the individually normalized (z-scored) BOLD value at the peak of the hemodynamic response was treated as the dependent variable.…”
Section: Integrated Eeg and Fmri Analysismentioning
confidence: 99%
“…As in perceptual studies, the feedback P3 may reflect update and storage of reward values for behavioral adjustment 25,[59][60][61][62] , by integrating them with internal models of a probabilistic task 63 . It may similarly reflect reward evidence accumulation dynamics 64 , possibly as a decision variable for strategic choice 65 .…”
Section: Value-based Feedback Erp Components Relevant To the Ipdmentioning
confidence: 99%